2017
DOI: 10.1142/s2010135x17500242
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron doping on structural and optical properties of TiO2thin film by sol–gel routed spin coating technique

Abstract: Thin films of iron (Fe)-doped titanium dioxide (Fe:TiO 2 Þ were prepared by sol-gel spin coating technique and further calcined at 450 C. The structural and optical properties of Fe-doped TiO 2 thin films were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), ultraviolet-visible spectroscopy (UV-vis) and atomic force microscopic (AFM) techniques. The XRD results confirm the nanostructured TiO 2 thin films having crystalline nature with anatase phase. The characterization results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…On the other hand, Eu ions doping has attracted much attention in photocatalytic process due to its higher photocatalytic activity than pure TiO 2 in the degradation of organic pollutants [ 11 ]. Thereby, recent studies have reported the photocatalytic enhancement of RE-doped TiO 2 thin films [ 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. TiO 2 photocatalyst can be used in slurry or immobilized systems [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Eu ions doping has attracted much attention in photocatalytic process due to its higher photocatalytic activity than pure TiO 2 in the degradation of organic pollutants [ 11 ]. Thereby, recent studies have reported the photocatalytic enhancement of RE-doped TiO 2 thin films [ 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. TiO 2 photocatalyst can be used in slurry or immobilized systems [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fe-doped TiO 2 NPs prepared by the hydrothermal method were applied as an efficient electron mediator for the fabrication of hydrazine chemical sensor using glassy carbon electrode [20] which proves to be a sensitive sensor. The sol-gel routed spin coating technique was employed to synthesize Fe-doped TiO 2 NPs and observed that the optical transmittance is was decreased with increasing Fe dopant concentrations [21]. Here, we chose the sol-gel method to synthesize Fe 2 O 3 -doped TiO 2 NPs in the presence of diethanolamine.…”
Section: Introductionmentioning
confidence: 99%
“…Transparent heat reflecting (THR) coating shows a wide opportunity in this field, specially when they possess high reflectance at the near infrared (IR) radiation and a high transmittance at the visible region which is a great alternative in solving the purpose [9,10]. For this purpose different metal/ metal oxides like SiO 2 [11], ZrO 2 [1,6,9], Al 2 O 3 [1], Cu 2 O [8], MgO [1], Fe [12], Ni [13], ZnO [1,14] are generally used as dopants in TiO 2 matrix for high reflecting material to enhance IR radiation for various applications. In addition, thin film of silver, gold and copper used as the metal in dielectric/metal/dielectric structures are studied as a potential material to reduce surface or inside room temperature by enhancing reflectance at the IR radiation solar spectrum for encourage energy saving building applications [8][9][10].…”
Section: Introductionmentioning
confidence: 99%